The Role of Artificial Intelligence in Enhancing Elementary School Students' Reading Interest: A Systematic Literature Review - Nurila Sari Ray; Yundi Fitrah; Adiopenta (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Reading interest plays a crucial role in the development of literacy skills among elementary school students. The advancement of Artificial Intelligence (AI) has led to various innovations in education, particularly in fostering students' engagement with reading materials. This study aims to analyze the impact of AI on improving reading interest in elementary students through a Systematic Literature Review (SLR) approach. Various studies from online databases were collected and reviewed to examine how AI-based tools influence reading motivation. The findings suggest that AI applications such as interactive storytelling, personalized learning assistants, and adaptive reading platforms significantly contribute to increasing students' enthusiasm for reading. However, challenges such as accessibility, teacher readiness, and content suitability remain key concerns. This study provides insights for educators and policymakers in integrating AI effectively to enhance early literacy development.